Application of the Six Sigma Method to Overcome Stock Warehouse Difference at PT United Tractors - Ramanta, Dhimi Yoga; Hidayat, Yusup Rachmat (Institut Ilmu Sosial dan Manajemen Stiami, 2023)
PT. United Tractors has a warehouse to support its business activities, storing goods in the warehouse. Problems that often occur in warehouses are stock differences and actual goods not matching the system. The aim of this research is to find the cause of the problem and overcome it. Six Sigma method with DMAIC (Define, Measure, Analyse, Improve, Control, and Evaluation) stages Used to overcome warehouse stock discrepancy problems. The subject of this research is a case study at PT. United Tractors East Jakarta. The dependent variable in this research is the Six Sigma method, and the independent variable is the difference in warehouse stock. The data used in the research are field studies and observations carried out in the PT warehouse. United Tractors East Jakarta The results of this research use the Six Sigma method to determine inventory control over stock discrepancy problems by going through stages. obtained results of 4 causes of stock discrepancy problems; the measurement stage looked for the highest percentage of values causing stock problems; from the high percentage results, the factors causing stock discrepancy problems were analysed; proposals for improvements were made that could have a good impact; and a monitoring stage was made of the factors causing stock discrepancy problems.